MENGGAGAS MODEL PENANGANAN PERDAGANGAN ANAK Dl SUMATRA UTARA - Ahmad Sofian (Populasi, 2006)
The province of North Sumatra is facing a crucial problem in child trafficking for prostitution. The responses to overcome this problem is insignificant while the case of child trafficking has grown rapidly lately. Many parties gain benefit from this illegal business, on the contrast the children lost their future as becoming the victims of this problem. This study aims to understand the perception and responses to overcome this problem in the future. The result shows that child trafficking for prostitution is still considered a new phenomenon. It is not surprising that the actions taken by the government is still very general, such as policies and program for prostitution in general while the victims are under aged children. There is no specific policies aimed to child trafficking. At the end, this study recommends the importance of intensive and comprehensive coordination of all relevantr institution in solving the crucial problem.